2017
DOI: 10.1186/s13567-017-0460-3
|View full text |Cite
|
Sign up to set email alerts
|

Global proteomic profiling of Yersinia ruckeri strains

Abstract: Yersinia ruckeri is the causative agent of enteric redmouth disease (ERM) of salmonids. There is little information regarding the proteomics of Y. ruckeri. Herein, we perform whole protein identification and quantification of biotype 1 and biotype 2 strains of Y. ruckeri grown under standard culture conditions using a shotgun proteomic approach. Proteins were extracted, digested and peptides were separated by a nano liquid chromatography system and analyzed with a high-resolution hybrid triple quadrupole time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 55 publications
1
14
0
Order By: Relevance
“…More recently, we identified differentially expressed proteins and global proteomic profiles of Y . ruckeri strains in order to elucidate proteomic biology and changes between strains 13 , 14 . There is an urgent need to understand the protein changes in the host lymphoid organs in response to Y .…”
Section: Introductionmentioning
confidence: 99%
“…More recently, we identified differentially expressed proteins and global proteomic profiles of Y . ruckeri strains in order to elucidate proteomic biology and changes between strains 13 , 14 . There is an urgent need to understand the protein changes in the host lymphoid organs in response to Y .…”
Section: Introductionmentioning
confidence: 99%
“…A study by Vikram et al indicates that purified citrus flavonoids can act as quorum sensing inhibitors, modulators of bacterial growth and inhibitors of type three secretion system component expression in Vibrio harveyi (Vikram et al, 2010). The presence of a type three secretion system in Y. ruckeri has recently been suggested by Kumar et al (2017), and a combination of general antimicrobial activities and inhibition of pathogenicity could thus be a plausible explanation for the observed reduction in pathogenicity. This would, however, require further studies into the exact molecular effects of the flavonoid supplement in question, and is therefore merely speculative for now.…”
Section: Discussionmentioning
confidence: 77%
“…FliG, the protein encoded by fliG , is located in the basal body C ring of the flagella (Passmore, Meas, & Marykwas, ). Kumar et al () have identified FliG in the SP‐O5 strain of Y. ruckeri belonging to BT1 but not in the other BT1 strain (CSF007‐82) and the two BT2 strains (7959‐11 and YRNC‐10) analysed in their study. Modification of FliG sequences of Escherichia coli and Salmonella spp.…”
Section: Discussionmentioning
confidence: 88%
“…The flagellum of the Enterobacteriaceae is a complex organelle, and nearly 50 genes are involved in its synthesis and functioning (Soutourina & Bertin, 2003). Several proteins involved in flagellar biosynthesis (FliC, FliG, FliH and FliN), in flagellar hook (FlgD, FlgE and FlgK) or in flagellar motor (MotB) have been identified in Y. ruckeri by proteomic analysis (Kumar, Hummel, Welch, Razzazi-Fazeli, & El-Matbouli, 2017). Evenhuis, LaPatra, Verner-Jeffreys, Dalsgaard, and Welch (2009) demonstrated that the absence of the flhA or flhE Summary Yersina ruckeri is an enterobacteria responsible for Enteric redmouth disease (ERM), which causes significant economic losses in the aquaculture industry worldwide.…”
mentioning
confidence: 99%